Financial Disruptions and the Cyclical Upgrading of Labor - Epstein, Brendan (IMF Working Papers; Working Paper, 2017)
Amid total factor productivity (TFP) shocks job-to-job flows amplify the volatility of unemployment, but the aggregate implications of job-to-job flows amid financial shocks are less understood. To develop such understanding we model a general equilibrium labor-search framework that incorporates on-the-job (OTJ) search and distinctly accounts for the differential impact of TFP and financial shocks. Surprisingly, we find that the interaction of OTJ search with financial shocks is sufficiently different from its interaction with TFP shocks so that, under standard calibrations, our model generates aggregate dynamics exceedingly in line with the behavior of key U.S. macro data across several decades and in the wake of the Global Financial Crisis as well. Importantly, as in the data, the model yields relatively high volatilities of consumption, labor income, and unemployment. As such, our work contributes to resolving two limitations of current general equilibrium labor-search theory: under standard calibrations models without OTJ search generate implausibly low unemployment volatility, while models with OTJ search generate unemployment volatility closer to the data but at the expense of implausibly low consumption and labor-income volatility.